Dampak Pengembangan Pariwisata di Pantai Ancol - Rizki Nurul Nugraha; Ananda Fadila Putri (Peneliti.net, 2023)
DKI Jakarta Province has various types of tourist options that tourists can visit, ranging from recreational parks, shopping centers, events, culinary tourism, cultural tourism and marine tourism. DKI Jakarta Province is also an area with the largest number of museums and places of historical relics coupled with the implementation of various tourism attractions as well as arts and cultural activities. in several areas that have met the requirements to be categorized as “Tourism Destinations” North Jakarta, whose territory is located on the coast, has added value in developing attractive tourism potential, not only for the people of Jakarta, but also for the wider Indonesian community. The North Jakarta government issued